German Revisionpolitik, 1919‑1933 - Fink, Carole (Historical Papers / Communications historiques, 1986)
AbstractGermany's revisionist policy in the interwar period constituted a prime source of international instability. From the Treaty of Versailles to the advent of Adolf Hitler, the statesmen of the Weimar Republic pursued a purposeful, nationalistic diplomacy aimed at eroding the treaty's main provisions. Revisionspolitik, which united most segments of the Reich public, was highly successful: the divisions among the former allies and Soviet Russia helped contribute to the achievements of the statesmen Rathenau, Stresemann and Bruning. By 1933 the Nazi regime, less prudent and more militant, was able to build on its predecessors' labours to regain German hegemony in Europe, supported by a nation grown accustomed to an irredentist foreign policy as welt as by diplomatic partners who had largely acquiesced in Berlin's revisionism. Though historians still differ over the style, methods, individual practitioners, and short- and long-term goals of Weimar foreign policy, it seems clear that it was the most pervasive, integral element of republican diplomacy.